Position and Content of Ministerial Regulations In the Perspective of the Presidential System - Hari Sanjaya (ISNU Sumatera Utara, 2024)
Regulatory obesity at the central and regional levels causes problems in the arrangement of legislation. The very diverse ministerial regulations make it difficult for local governments to follow up on them. The problems studied in this study are, first, what is the position and content of ministerial regulations in the perspective of legislation and the presidential system in Indonesia? Second, how are efforts to avoid obesity in the formation of ministerial regulations in the administration of government? The two problems will be analyzed descriptively qualitatively, using a legislative and conceptual approach. The results of this study conclude that, first, ministerial regulations are basically not included in the hierarchy of legislation, they can only be issued by ministers as long as there is authority or an order from a higher law to regulate them and only apply internally for the interests of the institutions they lead. However, ministers/ministries in the presidential system are not responsible to parliament but to the President, so the right person to determine the legislation should be the President; second, to avoid obesity in the formation of ministerial regulations, the president only needs to form a Government Regulation or Presidential Regulation, and does not need to delegate to ministers to form implementing regulations.